The Improvement of Protein Retention through a Higher Utilization of Carbohydrate in the Diet with Chromium for Common Carp Cyprinus carpio Linn. - S, Nuryati; Dana, D.; Malole, M.B.; Pasaribu, F.H. (Jurnal Akuakultur Indonesia, 2004)
Primary shrimp cell culture from lymphoid organ of Penaeus monodon was successfully developed. Minced tissues of lymphoid organ were seeded by tripsin enzyme and culture in Leibovit'z-15 supplemented with 10% fetal bovine serum and 5% NaCl. Plates were then incubated at 27 °C with 5% C02 supply. Confluent cells were infected by white spot baculovirus (WSBV). Cytopathic effect (CPE) induced by white spot baculovirus showed characteristics of detachment cells and lysis forming giant polycaryon cells. Primary shrimp cell culture could be continued by anvanced cell culture resulting cell line could be used virus media. Key words : cell culture, lymphoid organ, tiger shrimp, invitro, virus   ABSTRAK Kultur sel primer dari organ limfoid udang windu Penaaeus monodon telah berhasil dilakukan. Potongan organ limfoid dipisahkan menjadi sel-sel tunggal dengan menggunakan enzim tripsin. Sel-sel tunggal tersebut dikuitur dalam media Leibovit'z-15 dengan tambahan 10 % fetal bovine serum dan 5 % NaCl. Biakan diinkubasi pada suhu 27 °C dengan kandungan C02 sebanyak 5 %. Biakan yang telah konfluen diinfeksi dengan virus WSBV dan menghasilkan cytopathic effect (CPE) dengan karakter sel lepas dari perlekatan dan mengalami lisis yang menyisakan giant cells dengan inti banyak (polycaryons). Kultur sel primer ini dapat ditindaklanjuti dengan kultur sel dengan pasase yang berulang-ulang sehingga dapat menghasilkan sel lestari (cell line) untuk media tumbuh virus. Kata kunci: biakan sel, organ limfoid, udang windu, invitro, virus